Upaya Guru Dalam Mengaplikasikan Model Student Facilitator and Explaining Pada Pembelajaran Tematik Tema 6 di MIN 16 Aceh Barat - Abidah; Susi Susanti; Hanifuddin Jamin (eL Bidayah: Journal of Islamic Elementary Education, 2022)
Learning is a process of delivering knowledge carried out by the teacher. In the learning process, a teacher must be creative and innovative in choosing a learning model so as to create a pleasant learning atmosphere. The purpose of this study is to find out the teacher's efforts in implementing the Student Facilitator and Explaining learning model in Theme 6 Thematic Learning and to find out the obstacles experienced by teachers at MIN 16 West Aceh in thematic learning theme 6 by using the student facilitator and learning model. This research is a field research with a qualitative technical approach. In collecting data using interviews, observation and documentation as well as using qualitative analysis techniques. The results showed that the teacher's efforts in implementing the Student Facilitator and Explaining learning model in Theme 6 Thematic Learning at MIN 16 West Aceh were by the teacher explaining the learning competencies to be achieved, presenting the material, providing opportunities for students to explain their conclusions, and re-explaining the material. presented and concluded the learning material and finally closed the lesson. Furthermore, the obstacles faced in the application of the Student Facilitator and Explaining learning model are the different levels of student absorption and the allocation of short lesson hours so that students do not perform optimally in conveying the material in front of the class [Pembelajaran merupakan proses penyampaian ilmu yang dilakukan oleh guru. Dalam proses pembelajaran tersebut seorang guru harus kreatif dan inovatif dalam memilih model pembelajaran sehingga menciptakan suasana belajar yang menyenangkan. Untuk itu tujuan dari penelitian ini adalah untuk mengetahui upaya guru dalam penerapan model pembelajaran Student Facilitator and Explaining Pada Pembelajaran Tematik Tema 6 dan untuk mengetahui kendala-kendala yang dialami guru di MIN 16 Aceh Barat pada pembelajaran tematik tema 6 dengan menggunakan model pembelajaran student facilitator and explaining. Penelitian ini merupakan penelitian lapangan dengan pendekatan teknik kualitatif. Dalam pengumpupulan data menggunakan wawancara, observasi dan dokumentasi serta menggunakan teknik analisis kualitatif. Hasil penelitian menunjukkan bahwa upaya guru dalam penerapan model pembelajaran Student Facilitator and Explaining Pada Pembelajaran Tematik Tema 6 di MIN 16 Aceh Barat adalah dengan adanya guru memaparkan kompetensi pembelajaran yang hendak dicapai, menyajikan materi, memberikan kesempatan kepada siswa untuk memaparkan kesimpulannya, menerangkan kembali materi yang disajikan serta menyimpulkan materi belajar dan terakhir melakukan penutupan pelajaran. Selanjutnya kendala-kendala yang dihadapi pada penerapan model pembelajaran Student Facilitator and Explaining ini adalah tingkat daya serap siswa yang berbeda-beda serta alokasi jam pelajarannya yang singkat sehingga siswa tidak tampil maksimal dalam menyampaikan materinya di depan kelas]